Animal Models for Studying Post-Stroke Neuroplasticity - Risdiansyah Risdiansyah; Ahmad Ghiffari; Rury Tiara Oktariza; Fadhillah Putri Rusdi (Riviera Publishing, 2025)
Ischemic stroke remains one of the leading causes of long-term disability worldwide, with recovery dependent on the brain's neuroplastic potential. This review aims to evaluate the role of animal models in elucidating the mechanisms of neuroplasticity following stroke and their relevance to clinical application. Using qualitative literature analysis, the study synthesizes findings from various animal models including rodents, non-human primates, zebrafish, and Drosophila. Rodent models, particularly the middle cerebral artery occlusion (MCAO), have been instrumental in identifying key processes such as BDNF-driven synaptic remodeling, VEGF-induced angiogenesis, and glial involvement in tissue repair. Additionally, systemic modulators like the gut-brain axis, immune responses, and extracellular vesicles are increasingly recognized for their influence on recovery. Despite these insights, most studies disproportionately utilize young, healthy male animals, limiting their relevance to diverse patient populations with comorbidities and aging factors. The findings suggest a need for integrative, multimodal research that incorporates molecular techniques, imaging, and behavioral assays, along with cross-species validation, to improve translational outcomes. This review underscores the necessity of leveraging a broader spectrum of animal models and advanced methodologies to develop effective, personalized therapies for post-stroke rehabilitation.